(untitled) (Journal of Ideas in Health, 2024)
Background: The incidence and mortality rates of oral squamous cell carcinoma (OSCC) vary globally, yet the cancer continues to pose significant morbidity and mortality risks. This study sought to assess salivary IL-8 and IL-10 as biomarkers for identifying malignant oral lesions. Methods: Between March 2022 and May 2023, a case-control study at the Dental Center of New Baquba, Diyala, Iraq, collected saliva for IL-8 and IL-10 measurement via ELISA. An independent t-test compared IL-8 and IL-10 means based on age and gender, while ROC analysis gauged specificity and sensitivity. Results: The prevalence of OSCC was evenly distributed across genders, with a higher occurrence among patients aged over 55 years (87.5%). OSCC distribution in the oral cavity indicated the lips as the most affected area (40.0%), followed by the tongue (37.0%), and the hard and soft palate (12.50%). Statistically significant differences were noted in IL-10 and IL-8 levels between the study and control groups across all age brackets, except for IL-8 in the age ≤55 (p ≤ 0.05). Elevated mean levels of IL-10 and IL-8 were observed in the older age group (>55), with IL-10 showing a greater increase in males (71.99±3.6), while IL-8 levels were higher in females. IL-10 demonstrated higher sensitivity (90%) and specificity (60%) with an optimal cutoff point value of 43.29, whereas IL-8 exhibited a sensitivity of 80% and a specificity of 47.5% with an optimal cutoff point value of 44.48. Conclusion: Individuals aged over 55 showed higher IL-10 and IL-8 levels, particularly in males for IL-10 and in females for IL-8. Salivary biomarkers hold promise for early OSCC detection.